Performance Tradeoffs of Routing Protocols AODV And DSDV in Wireless Sensor Networks Using NS2 - Tarek Mosbah Abdala (Journal of Scientific and Human Dimensions, 2026)
Wireless Sensor networks are expected to play an important role in civilian and military settings where wireless access to wired backbone is either ineffective or impossible. Wireless sensor networks are effective in remote data acquisition. In this paper we conduct a survey of routing protocol properties of various wireless sensor network routing algorithms and analyzed them. The routing algorithms considered in this paper are classified into two categories proactive (table driven) and reactive (on demand). The algorithms considered are Ad-hoc On-Demand Distance Vector Routing (AODV) and Destination sequence Vector (DSDV) , the evaluation of routing protocols conducted using Ns-2 show that the proposed bandwidth-allocating congestion control and clustering mechanism are effective a WSN without any mechanism, in terms of Packet delivery ratio, throughput, and packet loss.
Keywords: Wireless Sensor Network; AODV; DSDV; Performance